2020
DOI: 10.1371/journal.pone.0233554
|View full text |Cite
|
Sign up to set email alerts
|

Human milk cortisol and immune factors over the first three postnatal months: Relations to maternal psychosocial distress

Abstract: Background Many biologically active factors are present in human milk including proteins, lipids, immune factors, and hormones. The milk composition varies over time and shows large inter-individual variability. This study examined variations of human milk immune factors and cortisol concentrations in the first three months post-partum, and their potential associations with maternal psychosocial distress. Methods Seventy-seven healthy mothers with full term pregnancies were enrolled, of which 51 mothers collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 70 publications
1
58
4
Order By: Relevance
“…Findings from previous studies investigating associations between experienced stress and GC level or rhythmicity in various samples [ 22 ], including serum [ 14 , 23 ], saliva [ 13 , 16 , 24 ], (early morning, spot or 24 h) urine [ 15 ], hair [ 25 ] and milk [ 12 , 26 , 27 ], were contradictory. There are several explanations for these different findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from previous studies investigating associations between experienced stress and GC level or rhythmicity in various samples [ 22 ], including serum [ 14 , 23 ], saliva [ 13 , 16 , 24 ], (early morning, spot or 24 h) urine [ 15 ], hair [ 25 ] and milk [ 12 , 26 , 27 ], were contradictory. There are several explanations for these different findings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, not only the number of samples is important, but also the timing of sampling. One study suggested that women with increased psychological stress collected their morning samples approximately three hours after awakening versus half an hour post-awakening in women with low stress experience [ 12 ]. Since GCs reach their highest value approximately 30–45 min after awakening, it might be possible that the lack of association could be attributed to between-group differences in sampling times [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two weeks after the stressful situation, the level of cortisol in milk was significantly higher. Moreover, breast milk also contains growth hormones [ 19 , 29 ].…”
Section: Milk and Bmdmentioning
confidence: 99%
“…Maternal stress may also be linked to child obesity [ 37 , 38 , 39 ], but the mechanisms explaining this link are largely unknown. We propose two main pathways that may explain this link during lactation (see Figure 1 ), that is, one physiological pathway (i.e., through human milk composition) [ 40 , 41 ] and one behavioral one (i.e., through maternal lifestyle and weight-related parenting) [ 42 , 43 ] affecting child weight-related behaviors [ 44 ]. Future research may examine whether and how intervention on maternal stress may impact human milk components and child weight outcomes through lactation-specific pathways (i.e., child satiety and eating characteristics, child gut microbiota, and flavor exposure).…”
Section: Future Intervention Research Agendamentioning
confidence: 99%